2014
DOI: 10.1139/cjce-2014-0077
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of sewer physical condition grading protocols for the City of Edmonton

Abstract: Condition assessment is a key component of successful asset management, and many diverse condition assessment protocols exist for sewer mains. These protocols are used to generate condition grades for sewer mains after inspection. Condition assessment protocols are important because renewal actions for sewers are prioritized based on condition grades. If condition grades assigned to sewers do not reflect actual pipe conditions close enough, the resulting allocation of resources will not be the best. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Therefore, the National Standardization Administration in China recently issued a project to update the protocol. In order to minimize the inaccuracy of sewer condition assessment, as a first step, it is necessary to make compressive comparisons between different protocols to gain a better understanding of the main reasons causing the different evaluation results and then to choose a better and more suitable protocol as a reference when updating the protocol [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the National Standardization Administration in China recently issued a project to update the protocol. In order to minimize the inaccuracy of sewer condition assessment, as a first step, it is necessary to make compressive comparisons between different protocols to gain a better understanding of the main reasons causing the different evaluation results and then to choose a better and more suitable protocol as a reference when updating the protocol [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The important factor of sewer system management is to allocate a budget for various activities including the inspection, repair, and maintenance of sewer pipes [1]. Since the cost of maintaining the sewer network must be balanced with the costs of other operations, prioritization is considered the most effective strategy [3]. Asset management is a formal system for determining the most cost-effective methods of sustaining the appropriate service level in the social infrastructure system [4].…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies on condition grading protocols for sewer pipelines including protocol comparison [3,6,7]. Canada's National Research Council (NRC) reported its comparisons of various condition grading protocols, including the WRc protocol and the protocol it developed in Edmonton and Winnipeg [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a lot of cities do not have data on the previous condition but also on the current sewer situation, which makes it impossible to assess the priorities of reconstruction [80] and, thus, makes the accuracy of the required maintenance budget more difficult. The task of determining the budget is a major problem in all sewer system maintenance activities [81]. One big challenge is that sewer pipes are underground, and it is very difficult to detect pipes that have an increased risk of cracks or of a malfunction of some other types.…”
mentioning
confidence: 99%